UI/UX DESIGN DEVELOPMENT ON PT GALVA TECHNOLOGIES Tbk WEBSITE SERVICE TRACKING WITH THINKING DESIGN METHOD - Anggi Oktaviani*; Dahlia Sarkawi; Jevan Yusuf; Deny Novianti (Jurnal Riset Informatika, 2025)
This research uses a qualitative approach with a focus on the development of the UI/UX design of the Galva Service Tracking website using the Design Thinking method. The main goal of this research is to improve the user experience by creating a more intuitive and efficient design. Here are the details of the methods used in this study. In addition, another purpose of this study is to develop a UI/UX design on the Service Tracking website of PT Galva Technologies Tbk using the Design Thinking method. With the application of information technology that is increasingly crucial, UI/UX design improvements are expected to increase user satisfaction and the effectiveness of the services provided. Through the Design Thinking approach, this research involves users in every stage of development starting from empathy, problem definition, ideation, prototype making, to testing. The System Usability Scale (SUS) method is used to evaluate the usability of a website. The results of the study show that the application of Design Thinking has succeeded in improving the quality of website design and function, as well as providing a better and more satisfying user experience. Thus, it is hoped that the Service Tracking website of PT Galva Technologies Tbk can meet the needs and expectations of users more optimally.